Petrography and geochemical signatures in cracks filling calcite sequences in septarian concretions, Sanganeh Formation, Kopet-Dagh basin, NE Iran - Mahboubi, A.; Moussavi-Harami, R.; Collins, Lindsay; Muhling, Janet (Asian Network for Scientific Information, 2010)
The objectives of this study were to understand the stages of crack-fill calcite in these concretions that can help in a better understanding of these secondary structures in NE Iran as well as other parts of the world. Petrography and stable isotopes signatures revealed that the septarian concretions are multiphase and display several stages of cementation (G2 to G4). The earliest carbonate matrix (septarian body, called G1) with d13C and d18O values of 0.01 and -21‰ PDB, respectively, precipitated from seawater during shallow burial and anaerobic microbial oxidation of organic matter. The formation temperature of G1 is calculated to be 15.5° C. The Presence of authigenic pyrite with G1 supports the interpreted environment of precipitation. Calcite from the walls to the central parts of the cracks (G2 to G4) showed increasing crystal sizes, clarity and depletion of d18O values. The formation temperature of G4 is calculated to be 54°C. The d13C values in three generations of calcite showed no major differences. These data revealed that the cracks are filled by calcite during burial, which the last generation formed at higher temperatures than the temperature of the nodules. © 2010 Asian Network for Scientific Information.